1968
DOI: 10.1017/s0022029900019105
|View full text |Cite
|
Sign up to set email alerts
|

The digestibility coefficients of myristic, palmitic and stearic acids in the diet of sheep

Abstract: SummaryThe apparent digestibility coefficients of the various constituents of diets containing myristic, palmitic or stearic acids have been determined in an experiment with 8 sheep.The inclusion of myristic acid in the diet had no effect on the digestibility coefficient of total dry matter or crude protein, but it decreased the digestibility coefficients of crude fibre and nitrogen-free-extractives and increased the digestibility coefficients of fat and minerals. When palmitic acid was included in the diet th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
2

Year Published

1972
1972
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 5 publications
3
25
0
2
Order By: Relevance
“…The diet supplemented with 7% coconut oil contained less cell wall constituents and more starch, but nevertheless digestibility of the cell wall constituents was not further reduced. Steele and Moore (1968) showed that the intake of 45 g myristic acid daily per sheep also had no effect on DM digestibility, but significantly decreased the digestibility of crude fiber and nitrogen-free-extract. However, in the present study the daily average intake of myristic acid was lower (6 and 9 g using 3.5 and 7% coconut oil, respectively) than in the study of Steele and Moore (1968).…”
Section: Effects Of Coconut Oil On Feed Intake Digestion and Metabolmentioning
confidence: 97%
See 1 more Smart Citation
“…The diet supplemented with 7% coconut oil contained less cell wall constituents and more starch, but nevertheless digestibility of the cell wall constituents was not further reduced. Steele and Moore (1968) showed that the intake of 45 g myristic acid daily per sheep also had no effect on DM digestibility, but significantly decreased the digestibility of crude fiber and nitrogen-free-extract. However, in the present study the daily average intake of myristic acid was lower (6 and 9 g using 3.5 and 7% coconut oil, respectively) than in the study of Steele and Moore (1968).…”
Section: Effects Of Coconut Oil On Feed Intake Digestion and Metabolmentioning
confidence: 97%
“…Steele and Moore (1968) showed that the intake of 45 g myristic acid daily per sheep also had no effect on DM digestibility, but significantly decreased the digestibility of crude fiber and nitrogen-free-extract. However, in the present study the daily average intake of myristic acid was lower (6 and 9 g using 3.5 and 7% coconut oil, respectively) than in the study of Steele and Moore (1968). In the study of McAllan et al (1983), 40 g d -1 coconut oil fed to sheep almost completely inhibited the ruminal digestion of both hemicellulose and cellulose.…”
Section: Effects Of Coconut Oil On Feed Intake Digestion and Metabolmentioning
confidence: 97%
“…A natureza "rúmen-inerte" da gordura protegida empregada (sais cálcicos de ácidos graxos de óleo de palma) provavelmente foi a responsável pela ausên-cia de efeitos na digestibilidade da fibra. Embora sais cálcicos de ácidos graxos não sejam totalmente inertes no rúmen (Sukhija & Palmquist, 1990;Wu et al, 1991), essa fonte, dentre as pesquisadas, é a que tem mostrado menor interferência na fermentação ruminal, o que pode ser atribuído à sua baixa solubilidade no rúmen. De acordo com revisão efetuada por Chalupa et al (2002), a taxa de lipólise (dissociação) ruminal de sais cálcicos de ácidos graxos de óleo de palma é de apenas 6%/h, com uma dissociação de 47% do total dos ácidos graxos.…”
Section: Table 3 -Apparent Digestibility Coefficients (%) Of Dry Mattunclassified
“…Ácidos graxos de cadeia curta têm mostrado maior redução na digestibilidade da fibra que ácidos graxos de cadeia longa (Steele & More, 1968;Macleod & BuchananSmith, 1972) e ácidos graxos livres causam maior efeito negativo que na forma esterificada (Macleod & Buchanan-Smith, 1972;Bateman & Jenkins, 1998). Bateman et al (1996), usando sebo, relataram redução no consumo de matéria seca de uma dieta com pouca fibra, mas não com dieta com alto teor de fibra, sugerindo que altos níveis de fibra na dieta promovem condições adequadas para o crescimento de microrganismos que hidrolisam e hidrogenam a gordura da dieta.…”
Section: Introductionunclassified
“…It was reported that calcium soaps containing long-chain fatty acids could be utilised for coating other feed particles to protect them against degradation in the rumen (Sklan and Tinsky, 1993). Moreover, supplementation of the diets of ruminants with hydrogenised triglyceride sources inhibits microbial activity in the rumen less than does supplementation with mono-or polyunsaturated fatty acid sources (Steele and Moore, 1968). Patton et al (2004) showed that supplementation with calcium soaps of fatty acids decreased hepatic lipid and increased liver glycogen content in transition dairy cows.…”
mentioning
confidence: 99%